Comparison of body size perception of young women in Korea and the United States. (21st April 2023) - Kim, Yoon-Sook; Suh, Jeffrey D; Kim, Jin Kook; Cho, Jae Hoon
ABSTRACT: Body size perception among young women in Asian and Western countries is believed to be quite different, however, there are no confirming studies. We analyzed the data from young women aged between 20 and 40 who participated in the National Health and Nutrition Examination Survey (2001–2018) of the United States (US) and Korea. US young women had higher rates of being overweight and obesity than Korean young women, and there was no significant change over 20 years. In both countries, the percentage of properly estimating one's own weight exceeded 70 percent and remained relatively steady. The percentage of overestimating one's own weight was only about 10 percent in Korea in 2001, but increased to 20 percent. In the case of the US, the percentage was about 15 percent in 2001–2002, but has since continued to decline. The percentage of underestimating one's own body weight was about 18 percent in Korea in 2001, but decreased to about 8 percent. In the case of the US, the percentage was very low at about 10 percent in 2001–2002, but gradually increased to about 18 percent in 2017–2018. In conclusion, young women in the US tend to underestimate their body size, and those in Korea tend to overestimate it.